Persepsi Pedagang Pasar Sipirok Tapanuli Selatan Terhadap Pembiayaan Bank Syariah - Muhammad Miftah Al-Qahtani; Ramadhani, Sri; Ahmad Syakir (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study explores the perceptions of market traders in Sipirok, South Tapanuli, regarding Islamic banking financing services. The findings reveal that most traders continue to rely on conventional banks or other traditional financial institutions, such as pawnshops, to meet their business capital needs. A lack of knowledge and limited outreach about Islamic banking are key factors behind the low adoption of these services among traders. Using a qualitative approach with a descriptive method, the study aims to analyze traders’ perceptions, identify the factors influencing their choice of financing sources, and uncover the obstacles that hinder the use of Islamic banking services. Data were collected through semi-structured interviews with 15 traders and analyzed using thematic analysis. The results indicate that the majority of traders hold less favorable views toward Islamic banking. Many perceive the profit-sharing system as more complex and less financially beneficial compared to the interest-based system used by conventional banks. Key factors influencing their choice of financing include ease of access, trust, and comfort in dealing with conventional banking services. Another major barrier is the lack of promotion and socialization efforts by Islamic banks. These findings suggest that Islamic financial institutions need to be more proactive in providing education, building personal relationships, and simplifying their messaging to make their services more accessible and appealing to small business owners such as market traders.